Improvement in exercise capacity and delayed anaerobic metabolism induced by far-infrared-emitting garments in active healthy subjects: A pilot study. (29th August 2020) - Mantegazza, Valentina; Contini, Mauro; Botti, Maurizia; Ferri, Ada; Dotti, Francesca; Berardi, Pierluigi; Agostoni, Piergiuseppe
Abstract: Background: Far-infrared-emitting garments have several biological properties including the capability to increase blood perfusion in irradiated tissues. Design: The aim of the study was to evaluate whether far-infrared radiation increases exercise capacity and delays anaerobic metabolism in healthy subjects. Methods: With a double-blind, crossover protocol, a maximal cardiopulmonary exercise test was performed in 20 volunteers, wearing far-infrared or common sport clothes, identical in texture and colour. Results: Comparing far-infrared with placebo garments, higher oxygen uptake at peak of exercise and longer endurance time were observed (peak oxygen uptake 38.0 ± 8.9 vs. 36.2 ± 8.5 ml/kg/min, endurance time 592 ± 85 vs. 570 ± 71 seconds; P < 0.01); the anaerobic threshold was significantly delayed (anaerobic threshold time 461 ± 93 vs. 417 ± 103 seconds) and anaerobic threshold oxygen uptake and anaerobic threshold oxygen pulse were significantly higher (25.3 ± 6.4 vs. 20.9 ± 5.4 ml/kg/min and 13.3 ± 3.8 vs. 12.4 ± 3.3 ml/beat, respectively). In 10 subjects the blood lactate concentration was measured every 2 minutes during exercise and at peak; lower values were observed with far-infrared fabrics compared to placebo from the eighth minute of exercise, reaching a significant difference at 10 minutes (3.6 ± 0.83 vs. 4.4 ± 0.96 mmol/l; P = 0.02). Conclusions: In healthy subjects, exercising with a far-infrared outfit is associated with an improvement in exercise performance and a delay in anaerobic metabolism. In consideration of the acknowledged non-thermic properties of functionalised clothes, these effects could be mediated by an increase in oxygen peripheral delivery secondary to muscular vasodilation. These data suggest the need for testing far-infrared-emitting garments in patients with exercise limitation or in chronic cardiovascular and respiratory patients engaged in rehabilitation programmes.